THE CASE OF TETORON YARNS BREAKING STRENGTH WHICH HAVE EXPERIENCED THE PRESERVATION OF PAPAYA LEAVES (Carica papaya), GUAVA LEAVES (Psidium guajava L) AND BETEL LEAVES (Xylocarpus moluccensis M.Roem) IN DIFFERENT DRYING TIMES - Marnita J Situmorang; Isnaniah '; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on July 2014, which is held in the Laboratory of fishing Gear Materials, Utilization of Water Resources, The Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this study was to know breaking strength of Tetoron yarns which have experienced the preservation of different extracts and drying times. This study used an experimental method by performing the experiments effect of Tetoron yarns which will experienced the preservation by the extracts of papaya leaves, guava leaves and betel leaves that were soaked in the equal concentration. The Breaking strength of yarns that used betel leaves in 10 days of drying times are higher than the yarns with both of the other extracts. It is caused by the tanin degree of betel leaves is higher than the other extracts, that is amount 20% of tanin degree. By the computation of ANAVA test obtained the result Fhit > Ftab, sig < 0,01, it means that there are the differences of Tetoron yarns breaking strength with different extracts soaking and drying times.Keyword : The breaking strength of yarns with different exstract soaking and drying times.